Cross-Country Evaluation of Protein Engineering Techniques for Disease Treatment - Eduardom, Charles; Amanda, Joo (Journal of Biomedical and Techno Nanomaterials, 2024)
Chronic and degenerative diseases have posed global challenges in the healthcare domain. Protein engineering techniques have emerged as a promising approach for developing effective protein-based therapies to address various diseases. However, the application of these techniques can vary across countries, depending on available resources, research infrastructure, and regulatory policies. This research aims to evaluate and compare the implementation of protein engineering techniques for disease treatment across different countries. Specifically, it analyzes the factors influencing the adoption of these techniques and identifies best practices and challenges faced in each country. This cross-country study involves data collection from various sources, including literature reviews, surveys, and interviews with experts in protein engineering and drug development. The data is analyzed both qualitatively and quantitatively to assess the level of adoption of protein engineering techniques, success in therapy development, and factors influencing progress in each country. The findings reveal that the adoption and success of protein engineering techniques for disease treatment vary across countries. Countries with adequate research resources, strong infrastructure, and supportive regulatory policies tend to have higher levels of adoption and success. In contrast, countries with limited resources and stringent regulations face challenges in effectively implementing these techniques. This research highlights the importance of international collaboration, technology transfer, and regulatory harmonization in promoting the global adoption of protein engineering techniques for disease treatment. By identifying best practices and addressing existing challenges, the potential of protein engineering techniques can be more widely leveraged to develop more effective and affordable therapies for patients worldwide.